Creep behavior of latania natural fiber‐reinforced epoxy composites at elevated temperatures. Issue 6 (25th March 2021) - Ghorbani, Javad; Daghigh, Vahid; Rahmati, Sadegh; Mahdian, Mahdi; Daghigh, Hamid
Abstract: Unique properties of natural fibers have made them strong sustainable materials in reinforcing composites. Latania natural fibers, recently compared to jute natural fibers, have shown a better mechanical performance in reinforcing polymer composites. Latania natural fiber‐reinforced epoxy (LFRE) laminated composites were studied under creep loads at elevated temperatures. The creep tests were performed at temperatures of 80 and 100°C and were subjected to 35% of the ultimate tensile strength. The failure time, initial strain, strain rate, and Larson–Miller constant for specimens were evaluated. The results suggested that change in temperature affected both the initial strain and the failure time. Scanning electron microscopy images were used to investigate the failure mechanisms of LFRE composites subjected to creep loads. The results of this study can be used as a benchmark in designing bio‐composite structures in which latania natural fibers are used.